Sildenafil potentiates the antitumor activity of cisplatin by induction of apoptosis and inhibition of proliferation and angiogenesis - El-Naa MM; Othman M; Younes S (Dove Medical Press, 2016)
Mona Mohamed El-Naa,1 Mohamed Othman,2,3 Sheren Younes4,5 1Faculty of Pharmacy, October University for Modern Sciences and Arts (MSA), 6 October City, Egypt; 2Preparatory Year College, University of Hail, Hail, Kingdom of Saudi Arabia; 3Faculty of Biotechnology, October University for Modern Science and Arts (MSA), 6 October City, Egypt; 4Pathology Department, Faculty of Medicine, Menoufia University, Shebin El-Kom, Egypt; 5College of Medicine, Princess Nora Bint Abdulrahman University, Riyadh, Kingdom of Saudi ArabiaAbstract: Sildenafil is the first phosphodiesterase-5 inhibitor used for the treatment of erectile dysfunction. However, recent studies have been suggesting an antitumor effect of sildenafil. The current study assessed the aforementioned activity of sildenafil in vivo and in vitro in solid-tumor-bearing mice and in a human cell line MCF-7, respectively. Moreover, we investigated the impact of sildenafil on cisplatin antitumor activity. The solid tumor was induced by inoculation of Ehrlich ascites carcinoma cells in female mice. The tumor-bearing mice were assigned randomly to control (saline), sildenafil (sildenafil 5 mg/kg/d, PO daily for 15 days), cisplatin (cisplatin 7.5 mg/kg, IP once on the 12th day of Ehrlich ascites carcinoma inoculation), and combination therapy (cisplatin and sildenafil) groups. The tumor volume was measured at the end of the treatment period along with the following parameters: angiogenin, vascular endothelial growth factor, tumor necrosis factor-α, Ki-67, caspase-3, DNA-flow cytometry analysis, and histopathological examination. The study results showed that sildenafil has significantly decreased the tumor volume by 30.4%, angiogenin and tumor necrosis factor-α contents, as well as vascular endothelial growth factor expression. Additionally, caspase-3 level significantly increased with sildenafil treatment, whereas Ki-67 expression failed to show any significant changes. Furthermore, the cell cycle analysis revealed that sildenafil was capable of improving the category of tumor activity from moderate to low proliferative. Sildenafil induced necrosis in the tumor. Moreover, the drug of interest showed cytotoxic activity against MCF-7 in vitro as well as potentiated cisplatin antitumor activity in vivo and in vitro. These findings shed light on the antitumor activity of sildenafil and its possible impact on potentiating the antitumor effect of conventional chemotherapeutic agents such as cisplatin. These effects might be related to antiangiogenic, antiproliferative, and apoptotic activities of sildenafil.Keywords: sildenafil, phosphodiesterase-5, breast cancer, angiogenesis, proliferation, apoptosis